ASPETAR clinical Guidelines: Safe Return to Sport during the COVID-19 Pandemic Version 2.0 (2021)
The Aspetar Clinical Guidelines are evidence-based clinical practice guidelines (`guidelines`) developed for sports medicine clinicians and patients in Qatar to inform decisions about the appropriate health care for specific clinical sports medicine conditions. [1] Although published and available online, these guidelines are specific to Aspetar, evidence-based, and created according to standardised best practice with specified creation and revision dates.